Harmonisation of transactions avoidance laws - Bork, Reinhard 1956-; Veder, Michael 1969- (Intersentia, 2022)
The book focuses on the harmonisation of transactions avoidance laws in the EU. Based on national reports from 24 jurisdictions and employing a principle-based approach, it proposes a new Model Law which, provides for legal certainty as to which transactions should (or should not) be challengeable in all Member States under the same conditions
Keywords: Bankruptcy / European Union countries; Corporation law / European Union countries